KONTRIBUSI KONSEP DIRI DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU SD KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - Yarniasti Maiyulita (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
Teacher’s performance is a sicnificant variable in gaining the school goals. Moreover, it is a means for measuring teachers and the school have reached educational aims. Based on a peli minery study, it is found out that the primary school teacher’s performance in the sub district of Bukit Sundi still low. The impact of this condition could be seen in their student’s achievement. One of the indicator is that their student’s average mark on the final examination is always in the lowest position compared of all of the scools in other sub districts in Solok Regency. A lot of variable might have affected the techer performance. Therefore, the objective of this study is to reveal how prominent the contribution of self concept and achievement motivation toward the primary school teacher’s performance in theses subdistrict of Bukit Sundi Solok Regency. The hypothesis of this study are : 1) self concept contributes toward teacher’s performance. 2) achievement contributes toward teacher’s performance. 3) self-concept and achievement motivation contribute simultanesusly toward teacher’s performance.